The Impact of Screen Time on Students Learning in Higher Education - Maryam Latif; Tuba Ali; Dr. Afshan Naseem , (Dialogue Social Science Review (DSSR), 2025)
This research looks into the impact of screen time on academic performance among female students in higher education in Pakistan. Through a quantitative approach with 116 female participants, the research reveals a weak positive correlation between screen time and Cumulative Grade Point Average (CGPA). Data of screen time, and academic performance was collected using a structured questionnaire. The reliability (α) value was 0.83 for screen time demonstrating high internal consistency. Validity was assured by experts’ review. The study highlights the need for interventions to promote healthier screen time habits and create conducive learning environments. The findings highlight that the use of incorporating digital literacy into the curriculum and have implications for educational institutions and policymakers and formulating policies to enhance digital well-being. As we go through the digital age, more study is necessary to investigate other elements impacting this relationship and improve the development of successful strategies for maximizing student learning experiences.